Formulation And Evaluation Of Phytosome Tablet Of Plant Mangifera Indica - Manish Dubey , Mrunal K. Shirsat (International Journal of Advanced Science and Technology, 2022)
The leaves of the Mangifera indica were collected, after authentification shade dried and powdered. To meet the quality standards, the dried powdered materials were subjected to various quality control parameters. Successive solvent extraction was done by using petroleum ether 60-80ºC, chloroform and methanol. Phytosome has been prepared by three methods i.e. Antisolvent precipitation technique, rotary evaporation technique and solvent evaporation technique. Characterization of phytosome successfully performed. Phytosomal complex tablets was prepared and determined their evaluation parameters i.e. weight variation, hardness, friability and disintegration time. Dissolution time study performed to observe percentage release of drugs.